2017
DOI: 10.18632/oncotarget.21091
|View full text |Cite
|
Sign up to set email alerts
|

ChickenCCDC152shares an NFYB-regulated bidirectional promoter with agrowth hormone receptorantisense transcript and inhibits cells proliferation and migration

Abstract: The chicken coiled-coil domain-containing protein 152 (CCDC152) recently has been identified as a novel one implicated in cell cycle regulation, cellular proliferation and migration by us. Here we demonstrate that CCDC152 is oriented in a head-to-head configuration with the antisense transcript of growth hormone receptor (GHR) gene. Through serial luciferase reporter assays, we firstly identified a minimal 102 bp intergenic region as a core bidirectional promoter to drive basal transcription in divergent orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The expression levels of lnc9141 and IRX5 at different tissues or stages may be determined by the methylation levels of CpG islands on both sides of the active region. Similarly, Lin et al 37 . demonstrated that chicken CCDC152 is oriented in a head-to-head configuration with the antisense transcript of growth hormone receptor (GHR) gene.…”
Section: Discussionmentioning
confidence: 95%
“…The expression levels of lnc9141 and IRX5 at different tissues or stages may be determined by the methylation levels of CpG islands on both sides of the active region. Similarly, Lin et al 37 . demonstrated that chicken CCDC152 is oriented in a head-to-head configuration with the antisense transcript of growth hormone receptor (GHR) gene.…”
Section: Discussionmentioning
confidence: 95%
“…In agreement with previous studies, ZP1 was highly expressed in the female chicken liver, which was indicated to be synthesized in the liver and transported via the bloodstream to the follicle (Bausek et al, 2000, 2004). CCDC152 , located on the W-chromosome, was highly expressed in the male kidney and liver, which was identified to reduce cell proliferation and migration through the JAK2/STAT signaling pathway in chicken (Lin et al, 2017). a PMM2 also had higher expression in male chickens, which was found in metabolic pathways such as amino sugar and nucleotide sugar metabolism and fructose and mannose metabolism (Kanehisa and Goto, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…GHR-AS-EST expression was the highest in the heart, followed by the liver, glandular stomach, and leg muscle, and it was the lowest in gizzard tissue ( Figure 1C). GHR-AS-EST suppresses GHR mRNA expression, but promotes the expression of both GHBP and 0.7-kb GHR The V1 GHR sense promoter reportedly drives the transcription of GHR sense transcript [27]. In this study, we identified an antisense promoter (ASP) of GHR located in intron 5 and 99 bp away from the 5′ end of GHR-AS-EST, which drives the expression of GHR-AS-EST (Figures 2A and S4).…”
Section: Ghr-as-est Is Strongly Expressed In Chicken Liver and Musclementioning
confidence: 73%
“…For qualitative analyses of the GHR V1 and ASP promoters, GFP luciferase reporters pV1-EGFP and pASP-EGFP were constructed by cloning the corresponding V1 and ASP regions into the pEGFP-N1 vector to substitute its CMV region, by PCR. The negative control vector pLinker-EGFP (without CMV region of pEGFP-N1) was constructed using deletion Ω-PCR as reported elsewhere [27]. To construct the Flag-tag expression plasmids, GH-CDS, GHR-FL-CDS, GHBP, 0.7-kb GHR and GHR-AS-EST were amplified by PCR from chicken liver cDNA.…”
Section: Construction Of Expression Plasmidsmentioning
confidence: 99%